1996
DOI: 10.1016/s0092-8674(00)81238-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Growth of Mice Lacking the Cyclin-Dependent Kinase Inhibitor Function of p27

Abstract: Disruption of the cyclin-dependent kinase-inhibitory domain of p27 enhances growth of mice. Growth is attributed to an increase in cell number, due to increased cell proliferation, most obviously in tissues that ordinarily express p27 at the highest levels. Disruption of p27 function leads to nodular hyperplasia in the intermediate lobe of the pituitary. However, increased growth occurs without an increase in the amounts of either growth hormone or IGF-I. In addition, female mice were infertile. Luteal cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
897
3
11

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,168 publications
(980 citation statements)
references
References 39 publications
65
897
3
11
Order By: Relevance
“…In the absence of p27 (p277/7) growth rates were also accelerated and body weights achieved values similar to p27+/+, hGHRH mice. These observations are consistent with those reported for the original MThGHRH (Hammer et al, 1985;Mayo et al, 1988) and p277/7 (Nakayama et al, 1996;Kiyokawa et al, 1996;Fero et al, 1996) mouse strains, indicating that alterations in the genetic background did not signi®cantly alter the e ect of hGHRH transgene expression or p27-de®ciency on body growth. Reduction or elimination of p27 (+/7 or 7/7) accelerated the growth promoting e ects of the MT-hGHRH transgene in both male and female mice, with the most dramatic e ects observed in p277/7, hGHRH mice ( Figure 1).…”
Section: Body Weightsupporting
confidence: 90%
See 2 more Smart Citations
“…In the absence of p27 (p277/7) growth rates were also accelerated and body weights achieved values similar to p27+/+, hGHRH mice. These observations are consistent with those reported for the original MThGHRH (Hammer et al, 1985;Mayo et al, 1988) and p277/7 (Nakayama et al, 1996;Kiyokawa et al, 1996;Fero et al, 1996) mouse strains, indicating that alterations in the genetic background did not signi®cantly alter the e ect of hGHRH transgene expression or p27-de®ciency on body growth. Reduction or elimination of p27 (+/7 or 7/7) accelerated the growth promoting e ects of the MT-hGHRH transgene in both male and female mice, with the most dramatic e ects observed in p277/7, hGHRH mice ( Figure 1).…”
Section: Body Weightsupporting
confidence: 90%
“…The p277/7 mice in this study displayed generalized organomegaly with disproportionate enlargement of the spleen, pituitary, testis and ovaries (Table 1A,B and Figure 2), as previously reported (Nakayama et al, 1996;Kiyokawa et al, 1996;Fero et al, 1996). In p27+/+, hGHRH mice, as in the original MT-hGHRH mouse strain (Hammer et al, 1985;Mayo et al, 1988), the pituitary, liver, spleen, heart and kidneys were increased in size, compared to their wildtype (p27+/+) littermates (Table 1A,B), with disproportionate enlargement of the pituitary and liver (Figure 2).…”
Section: Organ Weightssupporting
confidence: 89%
See 1 more Smart Citation
“…The importance of p27 Kip1 in the regulation of T-cell proliferation Nourse et al, 1994) has also been con®rmed by studies on p27 Kip1 -null mice (Fero et al, 1996;Kiyokawa et al, 1996;Nakayama et al, 1996). These animals were presented with increased proliferation of thymocytes, resulting in thymic hyperplasia and an increased responsiveness of splenic and thymic T-cells to IL-2, which, in turn, correlated with higher cyclin E-associated kinase activity.…”
Section: Discussionmentioning
confidence: 88%
“…First, it was reported that proteasome-mediated degradation of p27 protein occurred during the cell cycle and that this degradation was increased in a subset of tumors with poor prognosis (24,25). In addition, the generation of a murine model "null" for p27 revealed that knockout mice had a generalized hyperplasia and they were prone to the development of tumors (26,27). It was reported that normal prostate cells had abundant p27 protein and high levels of p27 messenger.…”
mentioning
confidence: 99%